2018
DOI: 10.1086/696619
|View full text |Cite
|
Sign up to set email alerts
|

Clear as Black and White: The Effects of Ambiguous Rhetoric Depend on Candidate Race

Abstract: Campaign advisors and political scientists have long acknowledged the benefits of ambiguous position-taking. We argue, however, that these benefits do not extend to black candidates facing non-black voters. When a white candidate makes vague statements, many of these voters project their own policy positions onto the candidate, increasing support for the candidate. But they are less likely to extend black candidates the same courtesy. We test these claims with an original two-wave survey experiment varying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 64 publications
1
17
0
Order By: Relevance
“…In the radio ad experiment, white voters punished the candidate for using such associative cues, and white respondents were ready to assume that Dave Wilson would prioritize members of the black community-such as by supporting affirmative action. These results build on Piston et al's (2018) findings that white voters project their own policy preferences onto white, but not black, candidates in cases of ambiguous position taking, and Lerman and Sadin's (2016) findings that white voters stereotype black candidates to have more liberal issue positions, while black voters do not uniformly do so.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In the radio ad experiment, white voters punished the candidate for using such associative cues, and white respondents were ready to assume that Dave Wilson would prioritize members of the black community-such as by supporting affirmative action. These results build on Piston et al's (2018) findings that white voters project their own policy preferences onto white, but not black, candidates in cases of ambiguous position taking, and Lerman and Sadin's (2016) findings that white voters stereotype black candidates to have more liberal issue positions, while black voters do not uniformly do so.…”
Section: Discussionsupporting
confidence: 56%
“…As a result of these signals, voters may assume that a candidate's policy positions are more in line with stereotypes about the political preferences of groups. The tendency to project these policy positions onto candidates may therefore depend on the ideological predispositions of the person receiving such cues (Lerman and Sadin, 2016;Piston et al, 2018). Such signals may be especially powerful in the low-information elections that decide the majority of elected offices in the U.S.…”
Section: Associative Racial Cuesmentioning
confidence: 99%
“…Lastly, we look only at reactions to white candidates. Work on ambiguous rhetoric (Piston et al 2018) suggests that extending this design to also vary the candidate's race and/or ethnic background might yield different results. But these limitations do not take away from the value of the present work as much as they reinforce our claim that this is a relatively understudied area that deserves more scholarly attention.…”
Section: Discussionmentioning
confidence: 99%
“…This is an additional reason for bringing the debate over the politics of bullshit into conversation with intersectional analysis of politics. (Kahn, 1992;Piston et al, 2018), in particular in how voters view their rhetoric, and their authority.…”
Section: Brexit Campaign Charactersmentioning
confidence: 99%
“…For example, a recent study of the impact of race on voter perceptions in the United States showed that white male candidates who spoke in vague generalities caused voters to "fill in the blanks", by projecting their own policy positions onto the candidate, and therefore increasing their likelihood to vote for them. Conversely, black male candidates who delivered vague comments were punished by their voters for this behaviour (Piston et al, 2018). Additionally, there are studies which show that voters tend to stereotype candidates based on their gender, bringing gendered assumptions about competence and authority into decisions about who to vote for (Huddy and Terkildsen, 1993;Kahn, 1992).…”
Section: Brexit Campaign Charactersmentioning
confidence: 99%